Developing entrepreneurial ecosystems in academia - Tunio, Muhammad Nawaz 1984-; Shaikh, Erum 1988-; Chaudhary, Kiran; Le Thanh Tiep (IGI Global, Information Science Reference, 2022)
Towards entrepreneurial university business sector HEI's of developing countries / Aasma Solangi -- The role of the university in entrepreneurial ecosystems : how to better integrate entrepreneurial education into a university curriculum / Yetkin Yildirim, Ahmet Guven -- Critical assessment of socio-intercultural entrepreneurship : a case on a postgraduate program in economics and international business / José Vargas-Hernández -- Carving new dimensions for entrepreneurial management : a qualitative inquiry from an Asian subcontinent region / Farhan Ahmed, Syed Faheem Bukhari, Abdullah Khan, Gohar Jamal, Hareem Moin, Mahnoor Aftab, Mahnoor Ikram, Yameena Baig -- Sociopreneurship-program of literation technology and academic assistance to MSMEs in increasing the sales market in industry Era 5.0 / Dwiza Riana, Arif Hidayat, Lia Mazia, Fachri Helmanto, Nurajijah Nurajijah -- Learning creativity and student's performance : the academia contributions / Orlando Manuel Lima Rua -- The impact of university curricula on financial education of millennials / José Vargas-Hernández -- Towards entrepreneurial university in developing countries / Adnan Pitafi, Aasma Solangi -- Socio-intercultural entrepreneurship capability building and development / José Vargas-Hernández -- Entrepreneurial success and opportunities for women and female youth in Pakistan : case study in Pakistani women university / Ghazala Jabeen, Farkhanda Manzoor -- Economic development and growth perspectives in entrepreneurship / Sadia Junejo, Adnan Pitafi, Arabella Bhutto
Includes bibliographical references and index
Keywords: Entrepreneurship / Study and teaching (Higher) / Developing countries; Electronic books; Entrepreneurship / Study and teaching (Higher); Developing countries; Entrepreneurship / 1.1 x; Hochschule / 1.2 x; Studium / 1.3 x; Unternehmensgründung / 1.4 x; Pakistan / 1.5 x; Entwicklungsländer / 1.6 x; Aufsatzsammlung